Serum vaspin levels and carotid intima‐media thickness in predialysis patients. (2nd April 2021) - Akyol, Aytac; Demirkıran, Davut; Akdag, Serkan; Naci Aldemir, Mehmet; Simsek, Hakkı; Ali Gumrukcuoglu, Hasan; Sahin, Musa; Emre, Habib
Abstract: Background and Objective: Visceral adipose tissue‐derived serine proteinase inhibitor (vaspin) is an adipokine that correlates with insulin resistance and obesity in human beings. Previous studies have evaluated the serum vaspin levels in several diseases such as chronic haemodialysis patients and coronary artery disease. To our knowledge, serum vaspin levels have not yet been reported in predialysis patients. Carotid intima‐media thickness (CIMT) is a noninvasive procedure to detect early atherosclerotic changes. The aim of this study was to evaluate serum vaspin levels in predialysis patients and their relationships with glomerular filtration rate and CIMT levels. Methods: A total of twenty‐five predialysis patients (14 females and 11 males) and 22 healthy subjects (8 females and 14 males) were enrolled in the study. Serum samples were subjected to the human vaspin RIA system. CIMT was measured by B‐mode ultrasonography. Results: Serum vaspin levels were significantly lower in predialysis patients than control subjects ( P < .05), while CIMT levels were significantly higher ( P < .001). Serum vaspin levels were found to be significantly correlated with glomerular filtration rate ( r = 0.42, P < .001) and CIMT ( r = −0.47, P < .05) in predialysis patients. Conclusions: This is the first report to describe the association between serum vaspin levels and CIMT in predialysis patients. We concluded that serum vaspin levels were decreased in predialysis patients than control subjects. In addition, serum vaspin levels were found to be significantly correlated with glomerular filtration rate and CIMT.